Synergistic enhancement of strength and bendability of Al-Mg-Si-Cu alloys for safety components by adding Mn - Yifeng Li; Zibin Wu; Dongtao Wang; Hiromi Nagaumi; Guoyi Zhang; Zhixin Feng; Xiuhua Luo; Yuanzhen Luo; Haitao Zhang; Bo Zhang (Materials & Design)
High-strength Al-Mg-Si-Cu alloys are difficult to use as safety components in the automotive field due to their poor bendability. In this study, the bendability of high-strength Al-Mg-Si-Cu alloys was improved significantly by the addition of Mn. It achieves a maximum bending angle of about 85°, while its yield strength and tensile strength reach 374 MPa and 405 MPa, respectively, and the elongation is about 15 % at T6. The excellent bendability of high-strength Al-Mg-Si-Cu alloys is attributed to two aspects: On the one hand, after the addition of Mn, a large amount of nano-micron dispersoids are precipitated. The dispersoids distributed uniformly in the matrix effectively pin dislocations and prevent grain boundary migration during deformation. Finally, the alloy obtains a large number of fibrous fine-grain regions and reduces the thickness of the peripheral coarse-grained surface layer. On the other hand, in the fibrous fine-grain regions, the dispersoids and a large number of grain boundaries effectively disperse the bending slip and avoid stress concentration. Finally, the adverse effect of the primary Fe-bearing particles on bendability is weakened. This work provides valuable insight and new methods to improve the bendability of high-strength Al-Mg-Si-Cu alloys.